Community empowerment for Sentani language preservation and cultural strengthening in Papua - Bernard Labobar; Yustinus Wangguway; Evelien F. Ugadje; Christina A. Jeujanan; Riski Tasijawa; Krislina Pattipeiluhu (Jurnal Abmas, 2026)
The decline in local language use and in children's awareness of local culture pose challenges for non-formal education. This community service activity aims to strengthen preservation of the Sentani language and promote local culture through contextual, participatory learning. The program was implemented at the Pusat Kegiatan Belajar Masyarakat (PKBM) Rotehbu, Sentani, Papua, involving faculty members, students from the Early Childhood Education Program, and learners through a Participatory Action Research (PAR) approach that emphasizes a collaborative cycle of action, observation, and reflection. The activity was designed to integrate Sentani language learning and local cultural practices by preparing papeda as an experiential, context-based learning medium. The results showed increased participants' engagement in using the Sentani language, strengthened understanding of local culture, and growing awareness and pride in cultural identity. Furthermore, this activity strengthened the partnership between academics and the community and provided students with a culturally-based learning experience within the context of community service. These findings confirm that integrating local languages, cultural practices, and non-formal education within the PAR framework is an effective strategy for supporting community empowerment and sustainable cultural preservation.   Abstrak Penurunan penggunaan bahasa daerah dan melemahnya pengenalan budaya lokal pada anak usia sekolah menjadi tantangan dalam pendidikan nonformal. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memperkuat pelestarian bahasa Sentani dan penguatan budaya lokal melalui pembelajaran kontekstual dan partisipatif. Program dilaksanakan di Pusat Kegiatan Belajar Masyarakat (PKBM) Rotehbu, Sentani, Papua, dengan melibatkan dosen, mahasiswa Program Studi PKAUD, serta murid melalui pendekatan Participatory Action Research (PAR) yang menekankan siklus aksi, observasi, dan refleksi secara kolaboratif. Kegiatan dirancang dengan mengintegrasikan pembelajaran bahasa Sentani dan praktik budaya lokal melalui pengolahan papeda sebagai media pembelajaran kontekstual berbasis pengalaman. Hasil kegiatan menunjukkan peningkatan keterlibatan aktif peserta dalam penggunaan bahasa Sentani, penguatan pemahaman budaya lokal, serta tumbuhnya kesadaran dan kebanggaan terhadap identitas budaya. Selain itu, kegiatan ini memperkuat kemitraan antara akademisi dan komunitas serta memberikan pengalaman pembelajaran berbasis budaya bagi mahasiswa dalam konteks pengabdian masyarakat. Temuan ini menegaskan bahwa integrasi bahasa daerah, praktik budaya, dan pendidikan nonformal dalam kerangka PAR merupakan strategi efektif dalam mendukung pemberdayaan komunitas dan pelestarian budaya secara berkelanjutan. Kata Kunci: bahasa Sentani; budaya lokal; pelestarian bahasa daerah; pendidikan nonformal; pengabdian masyarakat